Type Synthesis of Hybrid Robot Mechanism with 3T2R based on Single Opened Chain Unit - Sheng Weifeng; Chen Hai; Qin Youlei; Cao Yi (Jixie chuandong)
By analyzing the structures characteristics of the lower- mobility serial kinematic mechanism（SKM） and parallel kinematic mechanism（ PKM）,based on the linear independence theory of kinematic screws and taking of the lower- mobility SKM with single opened chain as unit,a systematic and effective type synthesis method is proposed for hybrid mechanism including the definition and symbol denotation method of both hybrid robots with a parallel mechanism and multi- parallel mechanisms. Firstly,the type synthesis of3T2 R 5- Do F SKMs with single opened chain are constructed based on the screw theory,then the type synthesis of 3T2 R hybrid mechanisms are accomplished by regarding PKM as a complex kinematic unit and replacing an equal DOF kinematic chain unit in lower- mobility SKM with single opened chain unit. Finally,other hybrid mechanisms are generated by the linear combination of the kinematic screw.